PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS TERHADAP AUDIT DELAY - Ulfah Ulfah; Endah Nurhawaeny (Jurnal Proaksi, 2019)
Abstract - The research method used in this study is a quantitative method because the research data in the form of numbers analysis using statistics to determine the effect of company size, profitability, solvency on audit delay.The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017 according to the total population of 70 companies that are late in submitting financial reports according to the criteria examined by purposive sampling technique so that the total sample data is 15 sample data. This study aims to: 1) Effect of company size on audit delay 2) Effect of Profitability on audit delay 3) Effect of solvency on audit delay. The results of the study show that (1) the regression coefficient of company size is equal to 34,540 The significance value of the variable firm size is greater than 0.05 which is equal to 0.738. The coefficient of determination and t count is 0.738 while t table is 1.1796. This shows that the first hypothesis is accepted (2) the regression coefficient of profitability which is equal to 86,052 The significance value of the Profitability variable is greater than 0.05 which is equal to 0.280. The coefficient of determination and the value of t count is 0, 0.936 while the t table is 1.1796. This shows that the second hypothesis is accepted (3) Solvability regression coefficient that is equal to 86,052 The significance value of the Profitability variable is greater than 0,05 which is equal to 0,513. The coefficient of determination and t count is 0.882 while t table is 1.1796. hypothesis accepted. Keywords: Audit Delay, Company Size, Provability, Solvability.